Barium in coal and coal combustion products: Distribution, enrichment and migration. Issue 3 (May 2022) - Hao, Huidi; Zhang, Minmin; Wang, Jinxi; Fu, Zhiheng; Balaji, Panchal; Jiang, Shuting
Coal triggering pollution caused by the emission of harmful substances in the process of coal combustion has been paid more and more attention. Barium is a ubiquitous heavy metal element in coal. During coal combustion, Ba in coal has been released into the environment in different forms, and coal-fired products with high Ba content can cause harm to the environment, human health and even pose a serious threat to life. By reviewing the literature, distribution, modes of occurrence, mobility of Ba in coal seams were summarized and studied in this paper. It is expected to provide information for controlling emission of Ba. The content characteristics of Ba in coal in some countries are introduced, and the content gradient of Ba in coal of Chinese different provinces is introduced in detail. And coal with Ba content greater than or equal to 5 times of the world average Ba content, namely, coal containing 750 μg/g Ba is called high Ba coal. Many studies have shown that Ba was extremely enriched in coal in some areas (up to 5, 000 μg/g), particularly in the Jurassic coal seams of the Huanglong coalfield in China. There were various types of occurrences of Ba in coal, including witherite, barite, crandallite and other minerals. Meanwhile, Ba can combine with organic matter as well. According to existing studies, the enrichment mechanism of Ba in coal is mainly derived from soil, sediment and seawater erosion, with the later causal minerals Ba carbonate and strontium rhodochrosite being the main carriers of Ba. The migration and transformation pathways of Ba in coal and its combustion products are described. As a medium volatile element, Ba is prone to concentrate in products of coal combustion, particularly those small-grainsize particles in fly ash, which may induce more serious contamination.